Analytic methods in sports using mathematics and statistics to understand data from baseball, football, basketball, and other sports - Severini, Thomas A. (Thomas Alan) 1959- (CRC Press, Taylor & Francis Group, 2020)
"Analytic Methods in Sports: Using Mathematics and Statistics to Understand Data from Baseball, Football, Basketball, and Other Sports, 2nd Edition provides a concise yet thorough introduction to the analytic and statistical methods that are useful in studying sports. It explains how to apply the methods to sports data and interpret the results, demonstrating that the analysis of sports data is often different from standard statistical analyses. The book integrates a large number of motivating sports examples throughout and offers guidance on computation and suggestions for further reading in each chapter."